A novel two-step enzymatic synthesis of blastose, a β-d-fructofuranosyl-(2↔6)-d-glucopyranose sucrose analogue. (15th July 2017) - Miranda-Molina, Alfonso; Castillo, Edmundo; Lopez Munguia, Agustin
Highlights: A novel two-step biosynthetic route to obtain blastose is described. Trehalose is regioselectively fructosylated by B. subtilis levansucrase. B. subtilis levansucrase may use sucrose or levan as fructosyl donor. Fructose is transferred to trehalose to yield O -β-d -Fru f -(2↔6)-trehalose. O -β-d -Fru f -(2→6)-trehalose is hydrolyzed by trehalase to yield blastose. Abstract: Blastose, a natural disaccharide found in honey, is usually found as a byproduct of fructo-oligosaccharide synthesis from sucrose with fructosyltransferases. In this study, we describe a novel two-step biosynthetic route to obtain blastose, designed from a detailed observation of B. subtilis levansucrase (SacB) acceptor structural requirements for fructosylation. The strategy consisted first in the synthesis of the trisaccharide O -β-d -Fru f -(2↔6)- O -α-d -Glc p -(1↔1)-α-d -Glc p, through a regioselective β-d -transfructosylation of trehalose (Tre) which acts as acceptor in a reaction catalyzed by SacB using sucrose or levan as fructosyl donor. In this reaction, levansucrase (LS) transfers regioselectively a fructosyl residue to either C6 -OH group of the glucose residues in Tre. The resulting trisaccharide obtained in 23% molar yield based on trehalose, was purified and fully characterized by extensive NMR studies. In the second step, the trisaccharide is specifically hydrolyzed by trehalase, to obtain blastose in 43.2% molar yield based on the trisaccharide. This is the first report describing the formation of blastose through a sequential transfuctosylation-hydrolysis reaction.